Searching and Displaying Bukhari’s Hadith from All Derivative Words Isim Makrifat in Quranpedia using Extreme Programming Method - Muhammad Althoof Nabalah; Eko Darwiyanto; Moch. Arif Bijaksana (STMIK Budi Darma, 2023)
Quranpedia is a website designed with a similar structure to Wikipedia. This website have goals to make it easier for users to find root words and verses of the Quran that contain this specific root. This study aims to evaluate the functionality of the Quranpedia website. The method used in this study is the black box testing method and the use of CodeIgniter 4. The results obtained from the testing reveal that the website achieves a high success rate of 97%, and the appearance of the resulting website proves to be user-friendly and in accordance with the presentation of the Bukhari Hadith. In addition, this study also tested word roots to see how accurate the search results for Bukhari Hadiths that have the same root word are. The results obtained from this test show that the accuracy rate is 83%. These results show that the website is very effective. Overall, this research demonstrates that Quranpedia effectively fulfills its main objective by providing a reliable and comprehensive reference source for the Muslim community. With a simple and user-friendly interface, as well as a commitment to continuously improve accuracy, Quranpedia is expected to be a valuable tool and can helping the Muslim community deepen their understanding and appreciation of hadith.